Screening for aphrodisiac property in local oyster of crassostrea Iredalei - Hashim, Ridzwan; Mohamaddiah, Hanani; Mohd Pauzi, Siti Norshuhadaa; Zulkipli, Farah Hanis; Tan Shau Hwai, Aileen (IDOSI Publication, 2013)
Oyster has been reputed since ancient time to increase sexual performance. This myth has been around for many years and still going strong until today. However, there is no scientific evidence to support the claim. Therefore, this study was conducted to screen the aphrodisiac property in local oyster of Crassostrea iredalei. Mounting behaviour and assessment of mating were the parameters tested in this study. Three doses; 50, 100 and 200 mg/kg from each aqueous and ethanol extracts of C. iredalei , respectively were administered (i.p.) to male mice for measuring both test parameters. Sildenafil citrate at the dose of 5 mg/kg was used as positive control while physiologic saline solution as negative control. Male mice treated with ethanol extract of C. iredalei showed substantial evidences in the mounting behaviour at the dose levels of 50, 100 and 200 mg/kg compared to aqueous extract. However, only mild aphrodisiac effect was showed with aqueous extract at the dose of 50 mg/kg. Besides, all doses of ethanol extract showed no significant differences ( p >0.05) after administration compared to the positive control. This indicated the ability of extract to be as competent as Sildenafil citrate at certain dosages even though Sildenafil citrate produced higher activities than the local oyster. No sperm was observable in all groups for the assessment of mating test. Thus, this study provided preliminary evidence regarding the potential aphrodisiac property of the local oysters that could be used as an alternative therapy to restore male sexual activity